Pengaruh social comparison terhadap body dissatisfaction pada laki-laki dewasa awal pengguna instagram - Afiya Dianar Najla; Uun Zulfiana (Fakultas Psikologi, 2022)
Early adulthood becomes one of the driving factors of individuals more oriented to appearance and make body shape as a benchmark in social media life. However, the comparison of appearances between individuals (social comparison) is unavoidable, causing body dissatisfaction to emerge. The purpose of this study was to determine the effect of social comparison on body dissatisfaction in early adult men who use instagram. This study uses a non-experimental quantitative approach and survey research techniques. The research subjects were 300 early adult males aged 20-30 years old and active users of social media instagram. The research scales used were Body Comparison Scale (BCS) and Body Shape Questionnaire (BSQ). The results of the simple linear regression analysis tests showed that there was a positive effect between social comparisons on body dissatisfaction with an R coefficient of 0.566 which indicates that when individual social comparison is high, their body dissatisfaction is also high, whereas when individu social comparison is low, their body dissatisfaction is also low. It is also known that social comparison has an effect of 32% on body dissatisfaction. Keywords: Body dissatisfaction, early adult males, instagram, social comparison